A systematic literature review on the international trends of indigenous peoples’ political participation - Banupriya Rathakrishnan; Banupriya Rathakrishnan; Kartini Aboo Talib Khalid; Kartini Aboo Talib Khalid; Sity Daud (Frontiers in Political Science)
IntroductionIndigenous Peoples play a vital role in democratic systems; however, their political participation is often hindered by structural barriers, including limited access to fundamental infrastructure and services, lack of formal recognition of land rights, and systemic discrimination. Despite the growing global discourse on Indigenous Peoples’ political participation, a comprehensive synthesis of international trends remains limited. This study aims to systematically review Indigenous Peoples’ political participation and highlight key themes that shape their participation in governance and advocacy.MethodsA systematic literature review was conducted following the PRISMA framework, analyzing 15 peer-reviewed articles that examine Indigenous Peoples’ political participation across different regions. Thematic analysis was employed to identify recurring patterns and key themes that characterize Indigenous political participation.ResultsFive primary themes emerged from the analysis: (1) land rights and political participation, which highlights the link between territorial claims and political participation; (2) indigenous governance and state relations, examining how Indigenous communities interact with governmental structures; (3) gender, identity, and political participation, addressing the unique challenges faced by Indigenous women; (4) digital activism and Indigenous mobilization, exploring the role of technology in fostering advocacy; and (5) environmental governance and climate justice, connecting Indigenous rights to broader ecological concerns.DiscussionThe findings contribute to the existing knowledge base by bridging gaps in the literature and offering insights into the structural challenges and opportunities for Indigenous political participation. This study underscores the need for more inclusive decision-making processes that recognize Indigenous rights and advocate for equitable representation. Future research should further explore the intersection of Indigenous political agency with digital activism, gender dynamics, and climate justice to inform policy frameworks that support Indigenous self-determination.